Nature for real: is nature a social construct? - Rolston, Holmes, 1932-2025, author; Edinburgh University Press, publisher (Colorado State University. Libraries, 1997)
Six words are model the world we view. But how far are these words for real? (1) "Nature," (2) "Environment," (3) "Wilderness," (4) "Science," (5) "Earth," and (6) "Value." "The world" is variously "constituted" by diverse cultures in their coping strategies, including our Western culture--so we are much reminded-- and the make-up of the words colors up what we see. More radically, many question whether humans can really know nature at all. If so, can we have a real environmental ethic?
Keywords: culture; biotic community; environmental values; environmental ethics; diversity; conservation